2010
DOI: 10.3791/1958
|View full text |Cite
|
Sign up to set email alerts
|

<em>In situ</em> Subcellular Fractionation of Adherent and Non-adherent Mammalian Cells

Abstract: Protein function is intimately coupled to protein localization. Although some proteins are restricted to a specific location or subcellular compartment, many proteins are present as a freely diffusing population in free exchange with a sub-population that is tightly associated with a particular subcellular domain or structure. In situ subcellular fractionation allows the visualization of protein compartmentalization and can also reveal protein sub-populations that localize to specific structures. For example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…24 hr after transfection of HEK293T cells with EBF3 expression constructs or pFLAG-CMV4-cassetteA (control vector), in situ subcellular fractionation was performed. 30 Cells were incubated with CSK buffer containing 0.1% Triton-X. The cytoplasmic extracts were removed, and proteins were precipitated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…24 hr after transfection of HEK293T cells with EBF3 expression constructs or pFLAG-CMV4-cassetteA (control vector), in situ subcellular fractionation was performed. 30 Cells were incubated with CSK buffer containing 0.1% Triton-X. The cytoplasmic extracts were removed, and proteins were precipitated.…”
Section: Figurementioning
confidence: 99%
“…30 We treated transiently transfected HEK293T cells expressing either EBF3 WT or one of the mutants (p.Asn66Asp, p.Tyr141Cys, p.Pro177Leu, p.Arg209Trp, or p.Gln305*) to extract cytoplasmic proteins and then selectively extracted non-tightly chromatin-bound proteins and free protein aggregates within the nucleus. Detection of FLAG-tagged EBF3 proteins by immunoblotting demonstrated that all mutants were present in both the cytoplasmic and nuclear fractions (Figure 3C).…”
mentioning
confidence: 99%
“…In preparing samples for microscopy, a pre-extraction procedure using CSK buffer was adopted to facilitate the removal of cellular constituents (such as soluble proteins) while permitting the retention of nuclear chromatin on a solid slide support [41]. Given that pre-extraction is widely applied in immunofluorescence studies and that the procedure is readily compatible with the detection of 8-POP DNA lesions (Figure 5), it is entirely conceivable that the two methods can be coupled to monitor the spatiotemporal dynamics of specific DNA damage response (DDR) proteins to sites of 8-POP-DNA damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…At 48 h posttransfection, coverslips were removed and placed in 6-well plates. Cells were sequentially extracted to remove cellular fractions as previously described (43). After each step, one coverslip for each transfection was removed and fixed in 3.7% formaldehyde to allow analysis of the retained proteins by immunofluorescence staining.…”
Section: Methodsmentioning
confidence: 99%